Checklist of the Elmidae (Coleoptera: Byrrhoidea) of Brazil - Segura, Melissa Ottoboni; Valente-Neto, Francisco; Fonseca-Gessner, Alaíde Aparecida (Zootaxa, 2012)
Information on the Elmidae that occur in a country is important for the advancement of ecological knowledge and the useof these organisms in biomonitoring programs. To date, there are checklists of elmids recorded in two regions of Brazil—one for the Amazon region, listing 48 species in 14 genera, and another for the state of Rio de Janeiro, listing 13 speciesin 7 genera. Thus, there is no checklist of the Elmidae for Brazil as a whole, and only inconsistent estimates of the numberof species present. Therefore, the aim of this paper is to present a checklist of the Elmidae recorded from Brazil. We basedthis checklist on literature produced between 1882 and 2011. A total of 148 species named plus 1 unnamed species ofElmidae are cited for Brazil, distributed in 24 genera. Moreover, we include taxonomic notes, such as changes in genus, and information about bibliography and distribution.